Profile of Farmers Based Feed Management and Animal Health of Bali Cattle in Agroecosystem Variation at Timor Island - Jefirstson Richset Riwukore; Asnath Maria Fuah; Luki Abdullah; Rudy Priyanto; Ahmad Yani; Bagus Priyo Purwanto; Fellyanus Habaora (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
The research objective was to determine the profile of smallholder farms based on the aspects of feed management and animal health in different agro-ecosystems on Timor Island. The research was carried out for 6 months, from June to December 2018. The research location was determined by purposive sampling, namely (1) pasture agroecosystem in District of Belu, Malaka, and Timor Tengah Utara, (2) agricultural agroecosystem in Kupang Regency and Kupang City, (3) plantation agroecosystems in Kupang Regency, and (4) forest agroecosystems in District of Timor Tengah Selatan. The purposive stratified proportional sampling method was used to determine the number of samples according to the Slovin formula at an error probability of 0.05 (5%) so that the sampling of respondents was 436 people. Types of data used are primary and secondary data with data methods by observation, interviews (questionnaires), and documentation. Descriptive quantitative data analysis described in a narrative manner. The results showed that for the aspect of feed management, feed preservation was only done by some farmers, with the highest to lowest percentage of actors being plantation agroecosystems (12.8%), agriculture, (5.9%), pasture (1.6%) and forest (0%). Whereas in the aspect of livestock health, the highest to lowest vaccination implementers were carried out in agricultural agroecosystems (98.0%) followed by plantations (92.2%), pasture (66.9%) and forests (44.8%).